Роль МРТ в диагностике забрюшинной лимфаденопатии при ангиомиолипоме и раке почки - Переверзев, А.С.; Щукин, Д.В.; Переверзев, Ю.А.; Антонян, И.М.; Мегера, В.В. (Онкологія, 2000)
Определяли информативность магнитно-резонансной томографии (МРТ) для диагностики истинного метастазированния рака и ангиомиолипомы почки в региональные лимфоузлы. Обследовано 97 больных: 21 — с ангиомиолипомой почки, 76 — раком почки. Критерием наличия лимфаденопатии служили размеры лимфоузла более 1 см. Региональная лимфаденопатия выявлена у 32 пациентов (в 3 случаях при ангиомиолипоме и в 29 — при почечноклеточном раке). МРТ обладает высокой точностью и чувствительностью в выявлении увеличения лимфоузлов, но не дифференцирует доброкачественную и злокачественную лимфаденопатию. Renal carcinomas have an apparent tendency towards metastasizing in retroperitoneal lymphatic collector. The purpose of this study was to assess the value of MRТ in diagnostics of actual involvement of regional lymph nodes in renal cell carcinoma and angiomyolipoma. Out of 97 patients studied, 21 were patients with angiomyolipoma of kidney and 76 were patients with renal cell carcinoma. As a criterion of lymphadenopathy, 1 cm or more magnification of lymph nodes’ size was used. Regional lymphadenopathy was revealed in 32 patients, including 3 patients with angiomyolipoma and 29 patients with renal cell carcinoma. MRТ was shown to be a highly accurate and sensitive method in diagnostics of magnification of lymph nodes but failed to differentiate between benign and malignant lymphadenopathies.